Sib risk of neural tube defect: is prenatal diagnosis indicated in pregnancies following the birth of a hydrocephalic child?. Issue 1 (February 1979) - Cohen, T; Stern, E; Rosenmann, A
Abstract : Recurrence frequencies of central nervous system malformations in sibs of probands with anencephalus or spina bifida range between 1% and 7%. The frequency of hydrocephalus among sibs of such probands is low (0.21%) but, nevertheless, is increased 2 to 5-fold when compared to general population frequencies. Anencephalus and spina bifida cystica were observed in 1.65% of sibs of children with hydrocephalus, a 2- to 8-fold increased over the population frequencies. These data indicate that some aetiological factors may be common to all three malformations. The risk figure of 1.65% for anencephalus and spina bifida in sibs born after the birth of a hydrocephalic proband constitutes sufficient indication for prenatal diagnosis by alphafetoprotein determination of the amniotic fluid.